2021
DOI: 10.1111/jerd.12710
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic navigation guided surgery and prosthetics for immediate loading of complete‐arch restoration

Abstract: Objective To assess clinical and radiological performance of novel digital workflow integrating dynamic guided surgery, to streamline execution of implant placement, soft and bone tissue sculpturing, and immediate delivery of navigation guided complete‐arch prosthesis. Materials and Methods This proof of concept prospective single cohort study investigated 10 consecutive patients (three males, seven females; mean age 62.5 ± 8.9 years; range, 48–75) requiring at least one complete‐arch fixed dental prostheses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Schnutenhaus et al 21 compared mean ISQ values between implants placed with s‐CAIS and alveolar ridge preservation (63 ± 8.75) and nonaugmented sites (64.12 ± 7.88). Other prospective and retrospective studies with s‐CAIS have only reported that all implants displayed values above the clinically acceptable thresholds of ITV 25 Ncm, RT 20 Ncm, or ISQ of 55 13,14,22–25 . With regards to d‐CAIS, Pozzi et al, 24 in a case series with 10 fully edentulous patients/60 implants, reported a mean ISQ of 71 ± 2.8.…”
Section: Methodsmentioning
confidence: 96%
“…Schnutenhaus et al 21 compared mean ISQ values between implants placed with s‐CAIS and alveolar ridge preservation (63 ± 8.75) and nonaugmented sites (64.12 ± 7.88). Other prospective and retrospective studies with s‐CAIS have only reported that all implants displayed values above the clinically acceptable thresholds of ITV 25 Ncm, RT 20 Ncm, or ISQ of 55 13,14,22–25 . With regards to d‐CAIS, Pozzi et al, 24 in a case series with 10 fully edentulous patients/60 implants, reported a mean ISQ of 71 ± 2.8.…”
Section: Methodsmentioning
confidence: 96%
“…The surgical templates were realized in order to fully guide the implant placement through metal sleeves that rigidly guide the dedicated drills. The clinicians were not allowed to change the pathway of the drills unless a freehand implant positioning was performed [7]. It is crucial to stabilize the surgical templates before the start of the bone drilling [8].…”
Section: Introductionmentioning
confidence: 99%
“…positioning was performed [7]. It is crucial to stabilize the surgical templates before the start of the bone drilling [8].…”
Section: Introductionmentioning
confidence: 99%
“…The pontic‐NSS technique was executed following the same surgical protocol, carving, and tinning the root‐shield as described above. The fresh alveolar sockets at the pontic sites were filled with a xenogeneic adsorbable bone substitute material (Bio‐Oss or Bio‐Oss Collagen, Geistlich Pharma), leaving at least 2.5 mm of space to the gingival margin to allocate the collagen matrix (Fibrogide, Geistlich Pharma) 45–48 . A horizontal mattress suture was used to keep in position the xenogeneic collagen matrix at the pontic site without compressing the gingival margins, just underneath the prosthetic contour to enhance the soft tissue regeneration, avoiding bone exposure.…”
Section: Methodsmentioning
confidence: 99%